2019
DOI: 10.1377/hlthaff.2018.05036
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Experiences Of Consumers Choosing Individual-Market Health Insurance Plans

Abstract: Joachim O Hero 1 [research fellow in health policy], Anna D. Sinaiko 2 [assistant professor of health economics and policy], Jon Kingsdale 3 [associate professor of the practice], Rachel S Gruver 4 [doctoral student in epidemiology], Alison A Galbraith 5 [associate professor of population medicine]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…Overall, our results were consistent with those of a survey among individuals enrolled in a single health plan, 34 which showed that approximately 60% of participants considered inclusion of a specific doctor or hospital when choosing a plan, although the researchers did not examine whether participants considered network status of mental health practitioners. We found that individuals were no more likely to check the network status of mental health practitioners than other specialists.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, our results were consistent with those of a survey among individuals enrolled in a single health plan, 34 which showed that approximately 60% of participants considered inclusion of a specific doctor or hospital when choosing a plan, although the researchers did not examine whether participants considered network status of mental health practitioners. We found that individuals were no more likely to check the network status of mental health practitioners than other specialists.…”
Section: Discussionsupporting
confidence: 85%
“…We first fielded a baseline survey after 2017 open enrollment that collected data about enrollee demographic and socioeconomic characteristics; additional description of methods and findings have been published previously (Hero et al, 2019). Twelve months later, we fielded a follow-up survey to baseline survey respondents to collect data about experiences in their 2017 plan, health experiences during 2017, and plan selection for 2018.…”
Section: Study Design and Datamentioning
confidence: 99%
“…Premium varies by number insured on a plan, so we controlled for family size, excluding families larger than five because of small numbers of these families in the sample. All analyses adjusted for poststratification weighting for sampling and nonresponse using methods published previously (Hero et al, 2019). In sensitivity analyses, we measured health status using self-reported health status instead of the presence of a chronic condition.…”
Section: Characteristics Associated With Plan Disenrollmentmentioning
confidence: 99%
“…However, this is still a challenge for most people because only 4% of the US population understands basic health insurance terminology [3]. In fact, Hero et al [35] showed that among people with low health insurance literacy, at least 54% had difficulty finding the best or most affordable plan, and at least 48% had fair or poor overall experience when choosing their plan. These findings suggest that disparities in the ability to access and understand health insurance information may be a reason why different demographics may have differing plan selections [36].…”
Section: Introductionmentioning
confidence: 99%